PHOTOCATALYTIC OPTIMIZATION OF MR DYE BY K-ZnO AND ZnO CATALYSTS UNDER VISIBLE IRRADIATION (FUDMA JOURNAL OF SCIENCES, 2021)
The lucubration on the visible light methyl red (MR) degradation using K-ZnO and undoped ZnO photo catalyst was investigated. The successive formation of K-ZnO was ascertained by several techniques such as scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), and UV-Visible spectrophotometer and solid state UV-Vis band gap energy determination by comparing the Kubelka-Monk equation with Tauc equation and the energy band gap was calculated to be 3.28ev. The influence of reaction variables such as MR concentration, reaction pH, catalyst loadings and temperature have been investigated for both process. The kinetics model was developed for both doped and undoped ZnO photocatalyst using pseudo first and second order kinetics, the result indicated that both doped and undoped ZnO followed pseudo first order kinetics due to higher correlation coefficient (R2) value of 0.985 and 0.922 with rate constant (k) of 0.026 min-1 and 0.062 min-1, respectively. Based on the rate constant value (k) obtained at different reaction temperatures, the Arrhenius expression was derived. The derived activation energy (Ea) for the degradation of MR by K-ZnO photocatalysis was 32.109x103JK-1. The optimum condition for K-ZnO showed nearly complete degradation (95%) of the dye molecules with slightly higher degradation efficiency compares to ZnO (91%).
Keywords: Methyl red; K-ZnO; Photo catalysis; Kinetics.